Reinventing ourselves: A conversation with Joyce E. King - Rodrigues, Tatiane Cosentino (Revista Eletrônica de Educação, 2015)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> DOI: http://dx.doi.org/10.14244/198271991229 Interview with Joyce E. King. Keywords: Joyce King, Black education, Alterity, Democratic practice.